Criminal Law Characteristics of Criminal Offences Under Article 190 of the Criminal Code of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2025)
Fraud exists in a wide range of social relations, including domestic, economic and other relations. At the same time, the development of technology and the emergence of new areas of economic relations (for example, virtual assets (cryptocurrencies) and cashless payments) contribute to the emergence of new techniques for committing fraud, while a low level of legal culture and selfish motives are the driving force behind the spread of fraudulent activities in social relations. The problem of preventing and combating fraud is particularly relevant in conditions of economic crisis or high inflation, martial law or a state of emergency, etc. In recent years, the number of such criminal offences has been on the rise.This article is devoted to the consideration of the main aspects of the criminal law characteristics of fraud as a criminal offence under Article 190 of the Criminal Code of Ukraine. The review includes an analysis of such components as the object, subject, objective and subjective aspects of fraud. In addition to reviewing the key characteristics of the relevant criminal offence, attention is paid to statistical data on the characteristics of the subject and quantitative indicators. In particular, statistics on combating fraud are provided in the context of the relationship between the number of registered offences, charges brought and quantitative indicators of convictions of offenders. The focus is on fraud, but additional general statistical data on offences also covered by Articles 189 and 191 of the Criminal Code of Ukraine are provided. In addition, a review of patterns identified on the basis of judicial and investigative practice using statistical methods in cases of criminal offences such as fraud committed by women has been carried out. The review of statistics is completed with a brief note on the analysis of judicial practice regarding fraud committed using electronic computing technology.
Keywords: criminal liability; criminal offences against property; fraud; review of court practice; Constitution of Ukraine.